Healthcare providers’ perspectives on implementing a brief physical activity and diet intervention within a primary care smoking cessation program: a qualitative study - Nadia Minian; Kamna Mehra; Mathangee Lingam; Rosa Dragonetti; Scott Veldhuizen; Laurie Zawertailo; Wayne K. deRuiter; Osnat C. Melamed; Rahim Moineddin; Kevin E. Thorpe; Valerie H. Taylor; Margaret Hahn; et al. (BMC Primary Care, 2024)
Abstract Background Post-smoking-cessation weight gain can be a major barrier to quitting smoking; however, adding behavior change interventions for physical activity (PA) and diet may adversely affect smoking cessation outcomes. The “Picking up the PACE (Promoting and Accelerating Change through Empowerment)” study assessed change in PA, fruit/vegetable consumption, and smoking cessation by providing a clinical decision support system for healthcare providers to utilize at the intake appointment, and found no significant change in PA, fruits/vegetable consumption, or smoking cessation. The objective of this qualitative study was to explore the factors affecting the implementation of the intervention and contextualize the quantitative results. Methods Twenty-five semi-structured interviews were conducted with healthcare providers, using questions based on the National Implementation Research Network’s Hexagon Tool. The data were analyzed using the framework’s standard analysis approach. Results Most healthcare providers reported a need to address PA and fruit/vegetable consumption in patients trying to quit smoking, and several acknowledged that the intervention was a good fit since exercise and diet could improve smoking cessation outcomes. However, many healthcare providers mentioned the need to explain the fit to the patients. Social determinants of health (e.g., low income, food insecurity) were brought up as barriers to the implementation of the intervention by a majority of healthcare providers. Most healthcare providers recognized training as a facilitator to the implementation, but time was mentioned as a barrier by many of healthcare providers. Majority of healthcare providers mentioned allied health professionals (e.g., dieticians, physiotherapists) supported the implementation of the PACE intervention. However, most healthcare providers reported a need for individualized approach and adaptation of the intervention based on the patients’ needs when implementing the intervention. The COVID-19 pandemic was found to impact the implementation of the PACE intervention based on the Hexagon Tool indicators. Conclusion There appears to be a need to utilize a flexible approach when addressing PA and fruit/vegetable consumption within a smoking cessation program, based on the context of clinic, the patients’ it is serving, and their life circumstances. Healthcare providers need support and external resources to implement this particular intervention. Name of the registry Clinicaltrials.gov. Trial registration number NCT04223336. Date of registration 7 January 2020 Retrospectively registered. URL of trial registry record https://classic.clinicaltrials.gov/ct2/show/NCT04223336 .